Pelatihan Kesiapsiagaan dan Tanggap Darurat Bagi Masyarakat Kelurahan Bungkutoko, Kota Kendari: Pengabdian - Dedy Oetama; Armid; Fahmiati; Muhammad Trial Fiar Erawan; La Ode Muhammad Arsal (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service aims to enhance the capacity of the Bungkutoko Village community, which is vulnerable to coastal disasters, through preparedness training and emergency response using a simulation method for first aid on drowning victims. The methods used include outreach to increase knowledge about risks and coastal disaster mitigation, as well as technical training through simulation of the first aid process involving victim identification, water rescue with the principles of reach, throw, row, go, and tow/carry, and cardiopulmonary resuscitation (CPR). The evaluation results show that this training significantly improves the community's knowledge and skills in administering first aid to drowning victims as well as increases emergency preparedness in coastal areas. This is demonstrated by the participants' ability to independently practice the simulated first aid procedures effectively, including CPR, which is highly relevant for reducing risks associated with water accidents. Simulation-based training effectively builds community preparedness in mitigating drowning disaster risks, thus it should be continued as an effort to enhance the resilience of disaster-prone coastal communities